J.M. Coetzee: Construction and Representation of Historical Reality (Effect) - Mittal, Nupur (Complutense Journal of English Studies, 2017)
South African novelist J.M. Coetzee has often been accused of refusing to engage with socio-political conflicts that mark his society. This paper will frame and analyse representation and conceptualization of history in Coetzee’s post-apartheid novels—Disgrace (2000) and Elizabeth Costello (2003). The central argument will be that, far from ignoring historical struggles and developments, Coetzee’s work engages with and encodes the same by using the grammar of novelistic discourse, which it positions as a rival to normative modern historical discourse.